Inhibited Intentionality: On Possible Self-Understanding in Cases of Weak Agency - Ingerslev, Line Ryberg (Frontiers in Psychology, 2020)
The paper addresses the question of how to approach consciousness in unreflective actions. Unreflective actions differ from reflective, conscious actions in that the intentional description under which the agent knows what she is doing is not available or present to the agent at the moment of acting. Yet, unreflective actions belong to the field in which an agent experiences herself as capable of acting. Some unreflective actions, however, narrow this field and can be characterized by intentionality being inhibited. By studying inhibited intentionality in unreflective actions, the aim of the paper is to show how weaker forms of action urge us to expand our overall understanding of action. If we expand the field of actions such that it encompasses also some of the involuntary aspects of action, we are able to understand how unreflective actions can remain actions and do not fall under the scope of automatic behaviour. With the notion of weak agency, the paper thus addresses one aspect of unreflective action, namely “inhibited intentionality” in which an agent feels a diminished sense of authorship in relation to her possibility for self-understanding. The notion of weak agency clarifies how agency itself remains intact but can involve a process of appropriation of one’s actions as one’s own. With a diachronic account of consciousness in unreflective action, the paper accounts for possible self-understanding in cases where none seems available at the moment of action.